PENGARUH FREKUENSI PENYIRAMAN AIR MENGGUNAKAN SPRINKLER TERHADAP RESPON FISIOLOGIS DAN PERTUMBUHAN SAPI PERANAKAN SIMMENTAL - Kusuma Adhianto; Siswanto (Siswanto); Citra Nindya Kesuma (Buletin Peternakan, 2015)
The objective of the research was to measure the effects of watering frequency using sprinkler on the physiological response and production of simmental grade cattle. Experiment was conducted during 45 days starting on December 2014 to January 2015 in Gunung Madu Plantation Cooperative farms, Gunung Batin district, Central Lampung regency. Feed analysis was carried out in the Laboratory of Animal Nutrition and Feed, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The experimental design used in this study was performed by using a Completely Randomized Design with treatment of control (P0), frequency of watering 1 time (P1) and frequency of watering 2 times (P2). Based on the results of research, we concluded that watering frequency treatment significantly (P<0.01) effected on the physiological response of Simmental grade cattle. However, treatment have not significantly effecting on consumption and growth of Simmental grade cattle.(Key words: Physiological response, Production, Sprinkler)